Caspase-1 and the inflammasome promote polycystic kidney disease progression - Swenson-Fields, Katherine I.; Ward, Christopher J.; Lopez, Micaila E.; Fross, Shaneann; Heimes Dillon, Anna L.; Meisenheimer, James D.; Rabbani, Adib J.; Wedlock, Emily; Basu, Malay K.; Jansson, Kyle P.; Rowe, Peter S.; Stubbs, Jason R.; et al. (Frontiers in Molecular Biosciences, 2022)
We and others have previously shown that the presence of renal innate immune cells can promote polycystic kidney disease (PKD) progression. In this study, we examined the influence of the inflammasome, a key part of the innate immune system, on PKD. The inflammasome is a system of molecular sensors, receptors, and scaffolds that responds to stimuli like cellular damage or microbes by activating Caspase-1, and generating critical mediators of the inflammatory milieu, including IL-1β and IL-18. We provide evidence that the inflammasome is primed in PKD, as multiple inflammasome sensors were upregulated in cystic kidneys from human ADPKD patients, as well as in kidneys from both orthologous (PKD1RC/RC or RC/RC) and non-orthologous (jck) mouse models of PKD. Further, we demonstrate that the inflammasome is activated in female RC/RC mice kidneys, and this activation occurs in renal leukocytes, primarily in CD11c+ cells. Knock-out of Casp1, the gene encoding Caspase-1, in the RC/RC mice significantly restrained cystic disease progression in female mice, implying sex-specific differences in the renal immune environment. RNAseq analysis implicated the promotion of Myc/YAP pathways as a mechanism underlying the pro-cystic effects of the Caspase-1/inflammasome. Finally, treatment of RC/RC mice with hydroxychloroquine, a widely used immunomodulatory drug that has been shown to inhibit the inflammasome, showed similar effects to Casp1 KO by protecting renal function specifically in female mice. Also, treatment with this drug restrained cystic disease in both male and female RC/RC mice. Collectively, these results provide evidence for the first time that the activated Caspase-1/inflammasome promotes cyst expansion and disease progression in PKD. Moreover, the data suggest that this innate immune pathway may be a relevant target for therapy in PKD.